IMPLEMENTASI SUMBER BELAJAR PADA ZAMAN RASULULLAH SAW UNTUK PENDIDIKAN YANG LEBIH BAIK - Huzdaeni Rahmawati (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2018)
The face of education in Indonesia at this time has been tarnished because of the failed products that have been produced. For example, there are many rampant corruptors around us. They are people who are highly educated,but have low conscience. Not only did the product fail, but in the process of education it also failed. We can see it from the relationship between educators, students, and parents who should support each other instead of blaming each other. Finally, education which should be a problem solver for the problems that arise, instead becomes a trouble maker in this country. This is what indicates that something is wrong with our education so far. Therefore, this paper will examine the learning resources at the time of the Prophet Muhammad SAW as a mirror of introspection for better education. As we know, the learning resources that existed at the time of the Prophet Muhammad were very limited, but could produce education that hacked into all the problems that existed in his day. This is different from the education of the present era whose learning resources are all sophisticated, but have not produced good education. With a literature review, the authors hope that writing can contribute to education in Indonesia to be even better.